Antiproliferative Effects of Ferulic, Coumaric, and Caffeic Acids in HepG2 Cells by hTERT Downregulation - Afsoon Afshari; Mahmoodreza Moein; Afshin Afsari; Zahra Sabahi (Advances in Pharmacological and Pharmaceutical Sciences)
Objective. Phenolic acids are well-known phytochemicals that are detected in a wide variety of medicinal plants, and their antiproliferative effects on cancer cells are known, but their mechanisms are poorly revealed. In most of cancer cells, telomerase reverse transcriptase (hTERT) is a dominant factor of telomere length regulation. The hTERT expression promotes invasiveness in tumor cells and is a hallmark of cancer. Therefore, in this study, the probable inhibitory effects of caffeic (Caf), coumaric (Cum), and ferulic acids (Fer) are investigated on the hTERT expression pattern in HepG2 cells. Methods. The MTT, apoptosis assays, and real-time PCR analysis were applied to evaluate viability, cytotoxicity, and hTERT gene expression level, respectively. Results. All of the studied phenolic acids showed cytotoxic effects on HepG2 cells in a timely manner and presented a time-dependent inhibitory effect on the growth of HepG2 cells. They reduced percentage of viable cells and induced apoptosis. Also, these phenolic acids had significant inhibitory effects on hTERT gene expression. Conclusion. These findings suggest that cell viability along with hTERT gene expression in HepG2 cells could be reduced by Cum, Caf, and Fer. As different cancer cells are resistant to conventional chemotherapeutics, this type of results proposes the telomerase as a proper target of cancer therapy development by natural products.